Hubungan Lingkungan Pendidikan dengan Prestasi Belajar Siswa Kelas XI MAS Muhammadiyah Nangahure - Jamil, Arfad Marici; Ernaningsih, Dian; Syafriati, Yulimira (Riwayat: Educational Journal of History and Humanities, 2025)
This investigation seeks to ascertain the relationship between components within the educational environment and the learning outcomes of 11th-grade learners at MAS Muhammadiyah Nangahure, a pursuit stemming from the impediments encountered by a number of pupils during the learning process, which are attributable to an inadequate learning setting. According to preliminary observations, the institution's topographical placement is alongside a main route that is heavily utilized by the surrounding population, causes a high intensity of disturbances from vehicle traffic, often disrupting students' concentration in the classroom. In addition, the presence of public facilities such as a soccer field near the school and the habit of the local community playing loud music also serve as external disturbances that affect students' concentration. This research applies a quantitative approach. The total number of participants for this investigation amounts to 63 individuals, of which 21 are XI grade learners, 21 parents or guardians of the students, and 21 members of the community around the school. Collection the information in this study was collected using questionnaires and documentation of odd semester report card grades for the 2024/2025 academic year. To ascertain the instruments' precision and stability, validation and dependability tests were carried out. The data gathered thereafter was analyzed through the application of multiple linear regression methods. The research outcomes reveal that on a simultaneous basis, the elements of the educational environment exert a significant effect on the learners' academic achievement (p 0.001), yielding a coefficient of determination of 61.1%. Partially, the school and societal settings demonstrate a significant bearing, whereas the domestic setting lacks a significant effect. These outcomes underscore the critical need for establishing a supportive learning environment, especially from the aspects of school and surrounding community, to optimally support students' academic achievements.